2003
DOI: 10.1002/gepi.10229
|View full text |Cite
|
Sign up to set email alerts
|

Association between lipoprotein lipase (LPL) gene and blood lipids: A common variant for a common trait?

Abstract: S447X, a serine substitution by a stop codon on base 99 of exon 9 of the lipoprotein lipase (LPL) gene, has beneficial effects on blood lipids. Other LPL alleles are associated with lipid levels, but whether one of these variants predominates remains elusive. We performed a systematic survey to identify single-nucleotide polymorphisms (SNPs) in all 10 LPL exons and flanking regions by resequencing the gene in 95 subjects. Of 24 variants, 14 were common (> or = 3%). We assayed the common SNPs in 186 cases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…The frequency we observed for the minor allele of 7754C>A (0.11) was similar to that reported by Morabia et al (8) (0.12). A significant association of the C allele with EH was observed ( Table 2), but was only confined to females ( p 0.027 for alleles, p 0.0315 for genotypes).…”
Section: C a Variantsupporting
confidence: 91%
See 1 more Smart Citation
“…The frequency we observed for the minor allele of 7754C>A (0.11) was similar to that reported by Morabia et al (8) (0.12). A significant association of the C allele with EH was observed ( Table 2), but was only confined to females ( p 0.027 for alleles, p 0.0315 for genotypes).…”
Section: C a Variantsupporting
confidence: 91%
“…On the other hand, Hunt and colleagues failed to replicate these positive findings in Caucasians (6). Because the genomic sequence of the LPL gene is highly polymorphic and a number of variants have been screened (7,8), associations of markers near the LPL gene locus and polymorphisms within this locus with hypertension have been tested in different populations. Ma and colleagues found that the D8S282 marker near the LPL gene locus contributed to the variance of SBP in healthy Chinese subjects from Hong Kong, especially in females (9).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the wild type, the LPL activity associated with the X447 mutation was higher in one, lower in another, but comparable in three studies [reviewed in 22]. In association studies, although the X447 allele has been reported to be associated with a favorable lipid profile in some studies [7][8]22] the results have not been confirmed in other studies [15]. Similarly, the association of the S447X polymorphism with CAD is inconsistent [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Several common LPL genetic variants have been widely studied, and among them HindIII in intron 8 (T→G at position 481), and S447X in exon 9 are of particular interest because of their common occurrence (25% and 9% of the less common alleles, respectively in most populations) and their associations with plasma lipid profile [6][7][8][9][10][11] and susceptibility to CAD [10][11][12][13][14][15] in several studies, although some inconsistent results have also been reported [16][17][18]. Since the HindIII polymorphism is located in the middle of intron 8, it is not considered to be functional but rather in linkage disequilibrium with a putative functional variant.…”
Section: Introductionmentioning
confidence: 99%
“…1998;Templeton et al 2000a,b;Morabia et al Step 3. Divide SNPs into LD groups: if two SNPs have r 2 Ն s, they belong to the same LD group.…”
mentioning
confidence: 99%